A coconut shell-based hierarchical porous carbon negative electrode material with radial pores and a nitrogen content gradient and a preparation method thereof
Patent Information
- Application Number
- CN202611334060.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-16
AI Technical Summary
采用额外碳包覆等方式虽然能够降低材料外表面的缺陷和孔隙,但可能堵塞离子传输通道,并增加工艺复杂程度
[0020] (1) The present invention achieves radial migration of salt and nitrogen sources through two-stage gradient freezing, and obtains a gradient precursor with low salt and low nitrogen in the outer layer and rich salt and nitrogen in the core, thus avoiding the uniform distribution of components caused by conventional blending.
Smart Images

Figure CN122916110A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a coconut shell-based hierarchical porous carbon anode material with radial pore size and nitrogen content gradient, belonging to the fields of new energy materials and electrochemical energy storage technology. Background Technology
[0002] With the rapid development of new energy vehicles, portable electronic devices, and large-scale energy storage systems, the requirements for high energy density, high rate performance, and long cycle life of lithium-ion batteries are constantly increasing. The anode material is a key component determining the capacity, initial coulombic efficiency, rate performance, and cycle stability of lithium-ion batteries. While traditional graphite anodes have advantages such as good cycle stability and low operating potential, their theoretical specific capacity is limited, and they are easily constrained by lithium-ion diffusion rates and interlayer intercalation kinetics under high-current charge-discharge conditions, making it difficult to simultaneously meet the demands for high capacity and high rate energy storage.
[0003] Biomass-based carbon materials, with their advantages of wide availability of raw materials, low cost, renewability, and abundant natural structures, are gradually becoming an important research direction for lithium-ion battery anode materials. Coconut shells, with their high fixed carbon content and relatively robust natural fibrous skeleton, can be carbonized to form carbon materials with a certain porous structure, making them an ideal raw material for preparing biomass-based anode materials. However, materials obtained by direct carbonization of coconut shells often suffer from insufficient pore quantity, unreasonable pore size distribution, discontinuous internal mass transfer channels, and a limited number of lithium storage active sites, thus limiting their reversible capacity and rate performance.
[0004] To improve the pore structure of biomass carbon materials, existing technologies typically employ methods such as physical activation, chemical activation, template-based pore formation, or molten salt-assisted carbonization. While chemical activation can significantly increase the specific surface area, it easily leads to the formation of numerous open micropores and surface defects. An excessively high specific surface area increases the contact area between the negative electrode material and the electrolyte, resulting in the formation of a larger solid electrolyte interface film during the initial charge-discharge process and consuming a significant amount of active lithium, thus reducing the initial coulombic efficiency. Simultaneously, overly developed pores also reduce the material's tap density, which is detrimental to improving the battery's volumetric energy density.
[0005] Molten salt-assisted carbonization utilizes the heat transfer, confinement, and template effects of molten salt to promote the formation of a biomass carbon framework, resulting in a porous structure after salt washing. Existing technologies can also add urea, thiourea, or other nitrogen-containing compounds during carbonization to introduce nitrogen-containing active sites into the carbon framework, thereby improving the material's lithium storage capacity. However, conventional mixing and carbonization methods typically result in a uniform or irregular distribution of salt and nitrogen sources in the precursor, leading to a lack of significant differences in porosity and nitrogen content between the shell and core of the resulting material. If the material surface also has high porosity and nitrogen doping levels, it easily increases surface defects and electrolyte side reactions, making it difficult to balance reversible capacity and initial coulombic efficiency.
[0006] Freeze-drying can preserve the pore structure of precursors using ice crystal templates, but current freeze-drying processes typically involve direct complete freezing, primarily for solvent removal and overall pore construction, making it difficult to effectively control the migration direction of salt and nitrogen sources during freezing. Ordinary freezing also tends to result in uneven ice crystal size and solute distribution, leading to poor pore structure consistency in the carbonized particles. While rapid freezing can refine ice crystals, simple rapid complete freezing also struggles to create a stable and controllable radial component gradient within spherical particles.
[0007] Furthermore, existing technologies typically involve immediately washing away the molten salt after carbonization followed by a secondary high-temperature treatment. Since the salt template has been removed, the internal porous carbon framework is prone to shrinkage or collapse during subsequent high-temperature processes. While methods such as additional carbon coating can reduce defects and porosity on the material's outer surface, they may block ion transport channels and increase process complexity. Therefore, existing biomass porous carbon anode materials still struggle to simultaneously achieve a low-defect, dense outer layer, a nitrogen-rich porous core, high initial coulombic efficiency, and good high-rate lithium storage performance.
[0008] Therefore, it is necessary to develop a new method for preparing coconut shell-based hierarchical porous carbon anode materials. By controlling the radial solute migration during the freezing process and utilizing the confined support effect of molten salt during the high-temperature reconstruction stage, the material can form a structure with a relatively dense outer layer, well-developed core pores, and nitrogen content increasing from the outside to the inside. This can improve the problem that existing biomass carbon anode materials cannot simultaneously achieve the desired initial coulombic efficiency, tap density, reversible capacity, and rate performance. Summary of the Invention
[0009] The purpose of this invention is to provide a method for preparing a coconut shell-based hierarchical porous carbon anode material with radial porosity and nitrogen content gradient, so as to solve the above-mentioned problems existing in the prior art.
[0010] This invention is achieved through the following technical solution: A method for preparing a coconut shell-based hierarchical porous carbon anode material with radial porosity and nitrogen content gradient, characterized by comprising the following steps: (1) Preparation of coconut shell-based molten salt-nitrogen blend slurry; (2) Preparation of coconut shell-based spherical freeze-dried precursors; (3) The coconut shell-based freeze-dried precursor was laid flat in a tube furnace and purged with N2. The temperature was first raised to 280-320℃ at 2-3℃ / min and held for 1 h. Then, the temperature was raised to 880-900℃ at 5-6℃ / min and held for 2 h for carbonization. Using a movable tube furnace, the molten salt sample was quickly pushed into the high temperature zone of 1040-1060℃ under N2 protection, with an average heating rate of 50℃ / min and held for 5 min. After holding, it was quickly moved into the water cooling zone and cooled to 600℃ at 25℃ / min. Then, it was cooled to room temperature with the furnace to obtain the thermally reconstructed product. The thermally reconstructed product was washed with water, vacuum dried, slightly depolymerized, sieved, and the particles were collected to obtain coconut shell-based hierarchical porous carbon.
[0011] As a preferred embodiment, the preparation method of the coconut shell-based molten salt-nitrogen blend slurry is as follows: Mature coconut shells are washed with deionized water, dried, and sieved to obtain coconut shell powder. The coconut shell powder, NaCl, KCl, and urea are mixed evenly, and deionized water is added to make the total solid content 25-30%. The mixture is then wet-milled with zirconia balls for 6 hours and stirred to make the sample evenly dispersed, finally obtaining a coconut shell-based molten salt nitrogen-containing mixed slurry.
[0012] As a preferred embodiment, the method for preparing the coconut shell-based spherical freeze-dried precursor is as follows: (1) The initial freezing temperature of the mixed slurry was measured using DSC. T f And establish the correspondence between freezing temperature, time and water phase freezing ratio based on the integral area of the freezing exothermic peak; (2) The slurry is atomized into 100-180 μm droplets through a dual-fluid nozzle and first enters the first freezing temperature zone (freezing temperature is...). T f -5.0 ℃, hold for 15 s); then transfer to the second freezing zone within 3 s (freezing temperature < T f Completely freeze at -25 ℃ and hold for 20 min, then freeze-dry to obtain spherical freeze-dried precursor.
[0013] As a preferred embodiment, the mass ratio of coconut shell powder to urea is (4-6):(1-3); the molar ratio of NaCl to KCl is 1:1.
[0014] As a preferred embodiment, the specific method for wet ball milling with zirconia balls for 6 hours is as follows: intermittent operation, with a 10-minute pause every 30 minutes for temperature control.
[0015] As a preferred embodiment, the size of the sieved and collected particles is 45–106 μm.
[0016] As a preferred embodiment, the coconut shell-based hierarchical porous carbon anode material with radial pores and nitrogen content gradient prepared by the aforementioned method is used in the preparation of lithium-ion battery anode sheets. The basic principle of this invention is as follows:
[0017] (1) By freezing in two stages, NaCl, KCl and urea migrate from the outer layer of the droplet to the inside and are fixed, forming a radial gradient with low salt and low nitrogen in the outer layer and high salt and nitrogen in the core.
[0018] (2) During the carbonization process, the molten salt in the core plays a role in confining support and creating pores, inhibiting the collapse of the carbon skeleton and pores, while allowing nitrogen to be preferentially anchored in the core.
[0019] (3) Rapid thermal reconstruction in the unwashed state causes defect repair and pore shrinkage in the outer layer, while the core pores are preserved under the support of molten salt; after washing, a dense shell-nitrogen-rich porous core structure is formed, thereby improving the first coulombic efficiency, reversible capacity and rate performance. Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention achieves radial migration of salt and nitrogen sources through two-stage gradient freezing, and obtains a gradient precursor with low salt and low nitrogen in the outer layer and rich salt and nitrogen in the core, thus avoiding the uniform distribution of components caused by conventional blending.
[0021] (2) The rapid thermal reconstruction without desalting is adopted to repair the defects in the outer layer and make it denser. At the same time, the molten salt confinement effect in the core is used to retain the porosity, so that a dense shell-porous core structure can be formed without additional carbon coating.
[0022] (3) The resulting material has low external surface defects, nitrogen-rich porous core and interconnected channels, which is beneficial to reduce electrolyte side reactions and improve the first coulombic efficiency, tap density, reversible capacity, rate performance and cycle stability. Attached Figure Description
[0023] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 This is a flowchart illustrating the preparation process of the coconut shell-based hierarchical porous carbon anode material of the present invention. Detailed Implementation
[0024] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention. Example 1
[0025] This embodiment provides a method for preparing a coconut shell-based hierarchical porous carbon anode material with radial porosity and nitrogen content gradient, specifically including the following steps.
[0026] (1) Preparation of coconut shell-based molten salt-nitrogen blend slurry Mature coconut shells were washed with deionized water, dried at 80 °C for 12 h, and then pulverized through a 100-mesh sieve to obtain coconut shell powder. 50.0 g of coconut shell powder was weighed and mixed evenly with 58.4 g of NaCl, 74.6 g of KCl (molar ratio 1:1, serving as both molten salt confinement medium and soluble pore-forming agent), and 20.0 g of urea (nitrogen source). Deionized water was added to bring the total solid content to 25%. The mixture was wet-milled at 400 r / min for 6 h using zirconia balls (ball-to-material mass ratio 8:1) (intermittent operation, with a 10-min pause every 30 min for temperature control). After milling, the mixture was stirred at 300 r / min for 30 min to ensure uniform dispersion. During this period, deionized water was added as needed to maintain a solid content of 25%, ultimately yielding a coconut shell-based molten salt nitrogen-containing slurry.
[0027] (2) Two-stage gradient freeze granulation and freeze drying A small amount of slurry was taken and the initial freezing temperature was measured by DSC (5 °C / min). T f = -4.2 ℃, and a corresponding relationship between freezing temperature, time, and aqueous phase freezing ratio was established based on the integral area of the freezing exothermic peak. The slurry was atomized into 100-180 μm droplets through a dual-fluid nozzle (orifice diameter 0.4 mm, atomization pressure 0.25 MPa, feed 4 mL / min), and first entered the first freezing temperature zone (-9.2 ℃, i.e. T f - At 5.0 ℃, held for 15 s, approximately 35% of the water in the droplet freezes; during this stage, ice crystals grow from the outside in, and NaCl / KCl and urea are expelled to the unfrozen area, forming a radial solute gradient with low salt and low nitrogen on the outside and high salt and high nitrogen on the inside. It then transfers to the second freezing temperature zone (-34 ℃, < T f - The sample was completely frozen at 25 °C and kept at that temperature for 20 min to fix the gradient structure. Finally, it was freeze-dried (-55 °C, ≤20 Pa, 30 h) to remove ice crystals and obtain a spherical freeze-dried precursor.
[0028] (3) Low-temperature stabilization and high-temperature molten salt confined carbonization-rapid thermal reconfiguration The freeze-dried precursor was laid flat in a tube furnace and purged with N2 (300 mL / min, 30 min). Then, it was heated to 300 °C at 2 °C / min and held for 1 h for low-temperature stabilization. This process initially dehydrated and crosslinked the coconut shell components, causing internal urea to decompose and condense to form nitrogen-containing intermediates. The spherical morphology and radial nitrogen distribution were initially fixed. Subsequently, it was heated to 900 °C at 5 °C / min and held for 2 h for carbonization. At this point, the NaCl-KCl eutectic salt melted, and the molten salt enriched within the particles provided confined support for the carbon framework, inhibiting pore collapse. The nitrogen source decomposition products reacted with the carbon framework, anchoring nitrogen primarily in the core.
[0029] After carbonization, the molten salt-containing sample was rapidly pushed into a pre-stabilized high-temperature zone of 1050 °C using a portable tube furnace (N2, 300 mL / min), with an average heating rate of 50 °C / min and a holding time of 5 min. During this stage, the outer shell, with its low salt content and lack of molten salt support, preferentially underwent defect repair and pore shrinkage under short-term high temperature, resulting in a denser structure. The molten salt confinement in the core slowed down the skeletal shrinkage, allowing the porosity to be preserved. After holding, the sample was quickly moved into a water-cooling zone and cooled to 600 °C at approximately 25 °C / min, followed by furnace cooling to room temperature. This rapid cooling locked in the asymmetric structure of a "dense shell-porous core".
[0030] (4) Salt washing, drying and finished product screening The thermally reconstructed product was washed in deionized water at 80 °C with a solid-liquid ratio of 1:20 for 1 h, repeated 3–5 times. The washing endpoint was defined as the absence of a white precipitate after adding AgNO3 to the final wash and a conductivity <50 μS / cm. The washing was placed after thermal reconstruction, allowing the molten salt in the core to continue its supporting and confining function during the short-term high-temperature phase. After the NaCl-KCl were dissolved by hot water, the original salt-occupied sites were transformed into interconnected pores. The product was vacuum dried at 100 °C for 12 h, then processed using a low-speed drum at 100 r / min for 10 min. Particles of 45–106 μm were collected after sieving, yielding coconut shell-based hierarchical porous carbon.
[0031] The prepared coconut shell-based hierarchical porous carbon active material was mixed at a mass ratio of active material:Super P:PVDF = 80:10:10, and NMP was used as solvent to prepare a slurry. This slurry was uniformly coated onto a copper foil current collector and vacuum dried at 80 °C for 12 h to obtain an electrode sheet. The surface loading of the active material was controlled at 1.0–1.5 mg / cm². A CR2032 coin cell (2026 type) was used for encapsulation, with a lithium metal sheet as the counter electrode and reference electrode, a Celgard 2400 polypropylene separator, and a 1 mol / L LiPF6 ternary mixed solution of EC / DMC / DEC (volume ratio 1:1:1). After battery assembly, the cells were allowed to stand for 12 h to eliminate residual interfacial stress and then subjected to constant current charge-discharge tests at a constant temperature of 25 ± 1 °C. Example 2
[0032] This embodiment provides a method for preparing a coconut shell-based hierarchical porous carbon anode material with radial porosity and nitrogen content gradient, specifically including the following steps.
[0033] (1) Preparation of coconut shell-based molten salt-nitrogen blend slurry Mature coconut shells were washed with deionized water, dried at 80 °C for 12 h, and then pulverized through a 100-mesh sieve to obtain coconut shell powder. 60.0 g of coconut shell powder was weighed and mixed evenly with 58.4 g of NaCl, 74.6 g of KCl (molar ratio 1:1, serving as both molten salt confinement medium and soluble pore-forming agent), and 25.0 g of urea (nitrogen source). Deionized water was added to bring the total solid content to 27%. The mixture was wet-milled at 400 r / min for 6 h using zirconia balls (ball-to-material mass ratio 8:1) (intermittent operation, with a 10-min pause every 30 min for temperature control). After milling, the mixture was stirred at 300 r / min for 30 min to ensure uniform dispersion. During this period, deionized water was added as needed to maintain a solid content of 27%, ultimately yielding a coconut shell-based molten salt nitrogen-containing slurry.
[0034] (2) Two-stage gradient freeze granulation and freeze drying A small amount of slurry was taken and the initial freezing temperature was measured by DSC (5 °C / min). T f = -4.6 ℃, and a corresponding relationship between freezing temperature, time, and aqueous phase freezing ratio was established based on the integral area of the freezing exothermic peak. The slurry was atomized into 100-180 μm droplets through a dual-fluid nozzle (orifice diameter 0.4 mm, atomization pressure 0.25 MPa, feed 4 mL / min), and first entered the first freezing temperature zone (-9.6 ℃, i.e. T f -5.0 ℃, held for 15 s), freezing approximately 35% of the water in the droplet; during this stage, ice crystals grow from the outside in, and NaCl / KCl and urea are expelled to the unfrozen area, forming a radial solute gradient with low salt and low nitrogen on the outside and high salt and high nitrogen on the inside. It then transfers to the second freezing temperature zone (-36 ℃, < T f The precursor was completely frozen at -25 °C and kept at that temperature for 20 min to fix the gradient structure. Finally, it was freeze-dried (-55 °C, ≤20 Pa, 30 h) to remove ice crystals and obtain a spherical freeze-dried precursor.
[0035] (3) Low-temperature stabilization and high-temperature molten salt confined carbonization-rapid thermal reconfiguration The freeze-dried precursor was laid flat in a tube furnace and purged with N2 (300 mL / min, 30 min). Then, it was heated to 280 °C at 2.5 °C / min and held for 1 h for low-temperature stabilization. This process initially dehydrated and crosslinked the coconut shell components, causing internal urea to decompose and condense to form nitrogen-containing intermediates. The spherical morphology and radial nitrogen distribution were initially fixed. Subsequently, it was heated to 880 °C at 6 °C / min and held for 2 h for carbonization. At this point, the NaCl-KCl eutectic salt melted, and the molten salt enriched within the particles provided confined support for the carbon framework, inhibiting pore collapse. The nitrogen source decomposition products reacted with the carbon framework, anchoring nitrogen primarily in the core.
[0036] After carbonization, the molten salt-containing sample was rapidly pushed into a pre-stabilized high-temperature zone of 1070 °C using a portable tube furnace (N2, 300 mL / min), with an average heating rate of 50 °C / min and a holding time of 5 min. During this stage, the outer shell, with its low salt content and lack of molten salt support, preferentially underwent defect repair and pore shrinkage under short-term high temperature, resulting in a denser structure. The molten salt confinement in the core slowed down the skeletal shrinkage, allowing the porosity to be preserved. After holding, the sample was quickly moved into a water-cooling zone and cooled to 600 °C at approximately 25 °C / min, followed by furnace cooling to room temperature. This rapid cooling locked in the asymmetric structure of a "dense shell-porous core".
[0037] (4) Salt washing, drying and finished product screening The thermally reconstructed product was washed in deionized water at 80 °C with a solid-liquid ratio of 1:20 for 1 h, repeated 3–5 times. The washing endpoint was defined as the absence of a white precipitate after adding AgNO3 to the final wash and a conductivity <50 μS / cm. The washing was placed after thermal reconstruction, allowing the molten salt in the core to continue its supporting and confining function during the short-term high-temperature phase. After the NaCl-KCl were dissolved by hot water, the original salt-occupied sites were transformed into interconnected pores. The product was vacuum dried at 100 °C for 12 h, then processed using a low-speed drum at 100 r / min for 10 min. Particles of 45–106 μm were collected after sieving, yielding coconut shell-based hierarchical porous carbon. Example 3
[0038] This embodiment provides a method for preparing a coconut shell-based hierarchical porous carbon anode material with radial porosity and nitrogen content gradient, specifically including the following steps.
[0039] (1) Preparation of coconut shell-based molten salt-nitrogen blend slurry Mature coconut shells were washed with deionized water, dried at 80 °C for 12 h, and then pulverized through a 100-mesh sieve to obtain coconut shell powder. 55.0 g of coconut shell powder was weighed and mixed evenly with 58.4 g of NaCl, 74.6 g of KCl (molar ratio 1:1, serving as both molten salt confinement medium and soluble pore-forming agent), and 25.0 g of urea (nitrogen source). Deionized water was added to bring the total solid content to 26%. The mixture was then wet-milled at 400 r / min for 6 h using zirconia balls (ball-to-material mass ratio 8:1) (intermittent operation, with a 10-min pause every 30 min for temperature control). After milling, the mixture was stirred at 300 r / min for 30 min to ensure uniform dispersion. During this period, deionized water was added as needed to maintain a solid content of 26%, ultimately yielding a coconut shell-based molten salt nitrogen-containing slurry.
[0040] (2) Two-stage gradient freeze granulation and freeze drying A small amount of slurry was taken and the initial freezing temperature was measured by DSC (5 °C / min). T f = -4.4 ℃, and a corresponding relationship between freezing temperature, time, and aqueous phase freezing ratio was established based on the integral area of the freezing exothermic peak. The slurry was atomized into 100-180 μm droplets through a dual-fluid nozzle (orifice diameter 0.4 mm, atomization pressure 0.25 MPa, feed 4 mL / min), and first entered the first freezing temperature zone (-9.4 ℃, i.e. -4.4 ℃). T f -5.0 ℃, held for 15 s), freezing approximately 35% of the water in the droplet; during this stage, ice crystals grow from the outside in, and NaCl / KCl and urea are expelled to the unfrozen area, forming a radial solute gradient with low salt and low nitrogen on the outside and high salt and high nitrogen on the inside. It then transfers to the second freezing temperature zone (-38 ℃, < T f The precursor was completely frozen at -25 °C and kept at that temperature for 20 min to fix the gradient structure. Finally, it was freeze-dried (-55 °C, ≤20 Pa, 30 h) to remove ice crystals and obtain a spherical freeze-dried precursor.
[0041] (3) Low-temperature stabilization and high-temperature molten salt confined carbonization-rapid thermal reconfiguration The freeze-dried precursor was laid flat in a tube furnace and purged with N2 (300 mL / min, 30 min). Then, it was heated to 300 °C at 3 °C / min and held for 1 h for low-temperature stabilization—the coconut shell components underwent initial dehydration and cross-linking, and the internal urea decomposed and condensed to form nitrogen-containing intermediates, thus initially fixing the spherical morphology and radial nitrogen distribution. Subsequently, it was heated to 900 °C at 5 °C / min and held for 2 h for carbonization. At this time, the NaCl-KCl eutectic salt melted, and the molten salt enriched inside the particles provided confined support for the carbon skeleton, inhibiting pore collapse. The nitrogen source decomposition products reacted with the carbon skeleton, anchoring nitrogen primarily in the core.
[0042] After carbonization, the molten salt-containing sample was rapidly pushed into a pre-stabilized high-temperature zone of 1070 °C using a portable tube furnace (N2, 300 mL / min), with an average heating rate of 50 °C / min and a holding time of 5 min. During this stage, the outer shell, with its low salt content and lack of molten salt support, preferentially underwent defect repair and pore shrinkage under short-term high temperature, resulting in a denser structure. The molten salt confinement in the core slowed down the skeletal shrinkage, allowing the porosity to be preserved. After holding, the sample was quickly moved to a water-cooling zone and cooled to 600 °C at approximately 25 °C / min, followed by furnace cooling to room temperature. This rapid cooling locked in the asymmetric structure of a "dense shell-porous core".
[0043] (4) Salt washing, drying and finished product screening The thermally reconstructed product was washed in deionized water at 80 °C with a solid-liquid ratio of 1:20 for 1 h, repeated 3–5 times. The washing endpoint was defined as the absence of a white precipitate after adding AgNO3 to the final wash and a conductivity <50 μS / cm. The washing was placed after thermal reconstruction, allowing the molten salt in the core to continue its supporting and confining role during the short-term high-temperature phase. After the NaCl-KCl were dissolved by hot water, the original salt-occupied spaces were transformed into interconnected pores. The product was vacuum dried at 100 °C for 12 h, then processed using a low-speed drum at 100 r / min for 10 min. Particles of 45–106 μm were collected after sieving, yielding coconut shell-based hierarchical porous carbon. Comparative Example 1: Normal freezing without rapid thermal remodeling
[0044] Except for the following steps, the amounts of raw materials and operating conditions were the same as in Example 1. After wet ball milling, a slurry with a solid content of 25% was atomized into droplets of 100–180 μm through a dual-fluid nozzle. Without performing a first-stage partial freezing, the droplets were directly sent to a -35 °C cold zone for complete freezing for 20 min, followed by freeze-drying for 30 h. The freeze-dried precursor was then subjected to stabilization at 300 °C and molten salt confinement carbonization at 900 °C. After carbonization at 900 °C for 2 h, it was directly cooled to room temperature without rapid thermal reconstruction at 1050 °C. Subsequently, it was washed with deionized water at 80 °C, dried, and sieved to obtain the material of Comparative Example 1. Comparative Example 2: Only two-level gradient freezing is performed
[0045] Except for the following steps, the amounts of raw materials and operating conditions were the same as in Example 1. A two-stage gradient freezing process was performed according to the method in Example 1: the droplets were first held at -9.2 °C for 15 s to allow approximately 35% of the water to freeze, then transferred to a -35 °C cold zone for complete freezing for 20 min, followed by freeze-drying for 30 h. The freeze-dried precursor was subsequently stabilized at 300 °C and then carbonized in a confined molten salt environment at 900 °C. After carbonization at 900 °C for 2 h, it was directly cooled without rapid thermal reconstruction at 1050 °C. The salt was then washed with deionized water at 80 °C, dried, and sieved to obtain the material of Comparative Example 2. Comparative Example 3: Rapid thermal remodeling with salt retention only
[0046] Except for the following steps, the amount of raw materials and operating conditions are the same as in Example 1. After wet ball milling, instead of performing a first-stage partial freezing, the atomized droplets are directly sent into a -35 ℃ cold zone for complete freezing for 20 min, followed by freeze drying for 30 h.
[0047] The freeze-dried precursor was sequentially stabilized at 300 °C and then carbonized in a molten salt confinement at 900 °C. After carbonization at 900 °C, the salt was not washed off. The temperature was increased to 1050 °C at an average heating rate of 50 °C / min and held for 5 min. Then, the temperature was reduced to 600 °C at an average cooling rate of 25 °C / min, and then allowed to cool naturally to room temperature. After cooling, the salt was washed off with deionized water at 80 °C, and the product was dried and sieved to obtain the material of Comparative Example 3. Comparative Example 4: Rapid thermal remodeling after salt washing
[0048] Except for the different order of hot water washing and rapid thermal remodeling, the operating conditions were the same as in Example 1. Two-stage gradient freezing, freeze-drying, stabilization at 300 °C, and molten salt confinement carbonization at 900 °C were completed according to the method of Example 1. After carbonization at 900 °C, the material was first cooled to room temperature, then washed with 80 °C deionized water to remove sodium chloride and potassium chloride, and vacuum dried at 100 °C for 12 h. The desalted carbon material was placed in a tube furnace preheated to 1050 °C, with an average heating rate of at least 40 °C / min, held at 1050 °C for 5 min, and then cooled to 600 °C at an average cooling rate of 25 °C / min to obtain the material of Comparative Example 4. Retaining molten salt during rapid thermal remodeling is a necessary condition for maintaining core channels and inhibiting excessive core shrinkage, rather than simply adding another 1050 °C heat treatment to achieve the same effect. Comparative Example 5: No urea added
[0049] Except for the absence of urea, the operating conditions were the same as in Example 1. 50.0 g of coconut shell powder, 58.4 g of sodium chloride, and 74.6 g of potassium chloride were weighed, without the addition of urea. Deionized water was added to adjust the slurry solid content to 25%, followed by wet ball milling, two-stage gradient freezing, freeze drying, stabilization at 300 °C, molten salt confinement carbonization at 900 °C, rapid thermal reconstruction at 1050 °C without desalination, hot water washing, drying, and sieving to obtain the material of Comparative Example 5. This comparative example was used to verify the effect of radial nitrogen content gradient on lithium-ion adsorption, surface wettability, rate capacity, and cycle stability. Comparative Example 6: No rapid cooling
[0050] The only difference between this comparative example and Example 1 is the cooling method after thermal reconstruction. The molten salt sample was rapidly heated to 1050 °C and held for 5 min. Instead of being moved to the water-cooling zone, the heating was stopped, and the sample remained in the high-temperature zone of the tube furnace. It was cooled to room temperature with the furnace at a flow rate of 300 mL / min. The average cooling rate during the 1050–600 °C range was approximately 5 °C / min.
[0051] Table 1. Comparison of performance differences between the examples and comparative examples. Comparative Example 1 246.8 0.58 46.1 / 47.0 2.70 / 2.76 78.4 456.2 268.0 80.2 Comparative Example 2 235.6 0.60 45.8 / 55.0 2.43 / 3.08 80.0 469.2 282.6 83.6 Comparative Example 3 188.9 0.65 40.1 / 42.0 2.68 / 2.73 81.5 432.7 294.1 86.8 Comparative Example 4 205.7 0.64 39.4 / 45.8 2.34 / 2.86 81.2 441.8 281.9 85.4 Comparative Example 5 160.8 0.74 37.7 / 52.1 0.55 / 0.60 83.9 389.6 266.3 88.6 Comparative Example 6 151.8 0.75 35.6 / 46.9 2.17 / 2.73 84.1 415.8 278.6 87.9 Example 1 174.6 0.72 38.2 / 52.7 2.36 / 3.12 85.2 449.5 327.2 93.2 Example 2 180.1 0.73 36.4 / 51.2 2.22 / 3.11 84.1 450.5 310.9 94.1 Example 3 177.1 0.71 37.1 / 50.9 2.21 / 3.09 85.2 440.9 312.9 93.9 As shown in Table 1, after two-stage gradient freezing in Comparative Example 2, the core porosity and nitrogen content were both higher than those in the shell, indicating that NaCl, KCl, and urea migrated into the droplet during partial freezing, forming preliminary radial pores and a nitrogen content gradient. However, due to the lack of rapid thermal reconstruction, the pores and carbon defects in the outer shell were not fully repaired, resulting in limited improvement in the initial coulombic efficiency and tap density.
[0052] Although Comparative Example 3 underwent rapid thermal reconstruction with salt retention, the distribution of salt and urea in the radial direction of the particles was relatively uniform due to the absence of two-stage gradient freezing, resulting in smaller differences in porosity and nitrogen content between the shell and the core. Its initial coulombic efficiency and tap density were improved, but its low current density capacity decreased, and its high rate capacity remained lower than that of Example 1.
[0053] In Comparative Example 4, the molten salt had been removed before rapid thermal reconstruction. The carbon skeleton in the core lost its molten salt support at 1050 °C, and some channels shrank or collapsed. Therefore, its core porosity, 1 A / g reversible capacity, and cycling stability were all lower than those of Example 1, indicating that "rapid thermal reconstruction in the undesalted state" is an important condition for maintaining a porous core.
[0054] Comparative Example 5, without the addition of urea, although it can form a dense shell-porous core structure and has a high tap density, has low nitrogen content in both the shell and core. The reversible capacity under 100 mA / g and 1 A / g conditions is significantly reduced, indicating that radially enriched nitrogen active sites have a positive effect on improving lithium storage capacity and rate performance.
[0055] Comparative Example 6, with furnace cooling, prolonged the material's residence time in the high-temperature zone, leading to further shrinkage of the carbon skeleton and closure of some core channels. This also resulted in the loss of some nitrogen-containing functional groups, consequently reducing specific surface area, core porosity, nitrogen content, reversible capacity, and rate performance. Although its tap density slightly increased due to skeleton shrinkage, its overall electrochemical performance was significantly lower than that of Example 1, indicating that rapid cooling plays a crucial role in locking in the dense shell-nitrogen-rich porous core structure.
[0056] Compared to Comparative Example 1, Example 1 showed a 6.8 percentage point increase in initial coulombic efficiency, an approximately 24.1% increase in tap density, and an approximately 22.1% increase in 1 A / g reversible capacity; its 100 mA / g reversible capacity remained at 98.5% of that of Comparative Example 1. The shell porosity of Example 1 was approximately 27.5% lower than that of the core, while the nitrogen content in the core was 0.76 at%, indicating that the material formed a relatively obvious dense shell-porous core and radial nitrogen content gradient.
[0057] Furthermore, Example 1 outperformed Comparative Example 2, which used only two-stage gradient freezing, and Comparative Example 3, which used only salt-preserving rapid thermal reconstruction, in terms of initial coulombic efficiency, tap density, rate capacity, and cycle stability. This indicates that the radial salt / nitrogen distribution formed by two-stage gradient freezing and salt-preserving rapid thermal reconstruction are not simply parallel relationships, but rather synergistic effects are generated through a continuous process of "gradient pre-construction - molten salt support - shell rearrangement - salt washing and pore formation".
[0058] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a coconut shell-based hierarchical porous carbon anode material with radial porosity and nitrogen content gradient, characterized in that, Includes the following steps: (1) Preparation of coconut shell-based molten salt-nitrogen blend slurry; (2) Preparation of coconut shell-based spherical freeze-dried precursors; (3) The coconut shell-based freeze-dried precursor was laid flat in a tube furnace and purged with N2. The temperature was first raised to 280-320℃ at 2-3℃ / min and held for 1 h. Then the temperature was raised to 880-900℃ at 5-6℃ / min and held for 2 h for carbonization. Using a movable tube furnace, the molten salt sample was quickly pushed into the high temperature zone of 1040-1060℃ under N2 protection, with an average heating rate of 50℃ / min and held for 5 min. After holding, it was quickly moved into the water cooling zone and cooled to 600℃ at 25℃ / min. Then it was cooled to room temperature with the furnace to obtain the thermally reconstructed product. The thermally reconstructed product was washed with water, vacuum dried, slightly depolymerized, sieved, and the particles were collected to obtain coconut shell-based hierarchical porous carbon. The preparation method of the coconut shell-based molten salt-nitrogen blend slurry is as follows: Mature coconut shells are washed with deionized water, dried, and sieved to obtain coconut shell powder. The coconut shell powder, NaCl, KCl and urea are mixed evenly, and deionized water is added to make the total solid content 25-30%. The mixture is wet-milled with zirconia balls for 6 hours and stirred to make the sample evenly dispersed, finally obtaining a coconut shell-based molten salt nitrogen-containing mixed slurry. The mass ratio of coconut shell powder to urea is (4-6):(1-3); the molar ratio of NaCl to KCl is 1:1; The specific method for wet ball milling with zirconia balls for 6 hours is as follows: intermittent operation, with a 10-minute pause every 30 minutes for temperature control. The method for preparing the coconut shell-based spherical freeze-dried precursor is as follows: (1) The initial freezing temperature of the mixed slurry was measured using DSC. T f And establish the correspondence between freezing temperature, time and water phase freezing ratio based on the integral area of the freezing exothermic peak; (2) The slurry is atomized into 100-180 μm droplets through a dual-fluid nozzle and first enters the first freezing temperature zone (freezing temperature is...). T f -5.0 ℃, hold for 15 s); then transfer to the second freezing zone within 3 s (freezing temperature < T f Completely freeze at -25 ℃ and hold for 20 min, then freeze-dry to obtain spherical freeze-dried precursor.
2. The method for preparing a coconut shell-based hierarchical porous carbon anode material with radial porosity and nitrogen content gradient as described in claim 1, characterized in that, In step (3), the size of the sieved and collected particles is 45-106 μm.
3. The coconut shell-based hierarchical porous carbon anode material with radial porosity and nitrogen content gradient prepared by the preparation method according to any one of claims 1 to 2 is used in the preparation of lithium-ion battery anode sheets.